Identifikasi Penyimpanan, Penyajian, Kandungan Rhodamin-B serta Angka Lempeng Total pada Getuk Pisang: Studi di UD. X Pusat Oleh-Oleh - Putri, Della Meyke; Moelyaningrum, Anita Dewi; Ellyke, Ellyke (Pustaka Kesehatan, 2024)
The high number of cases due to food poisoning caused by food contaminated by chemicals or biological contamination due to the application of hygiene and sanitation during storage and serving are not given much attention. This study aimed to identify storage, serving, the content of Rhodamine B, and Total Plate Count (TPC) in getup pisang at the souvenir center of Y District. This is a descriptive study with data collection through observation and laboratory tests. Samples are 6 brands of getuk pisang marketed at UD. X souvenir center of Y District. The result showed that 92.3% have good hygiene storage conditions, and 100% have implemented the requirements of well-serving packaging. The laboratory test showed that all samples do not contain Rhodamine B and fulfill for the total plate count requirement. In conclusion, the storage and serving condition of getuk pisang at UD. X souvenir center of Y District were in good condition, and all samples do not contain Rhodamine B and fulfill for the total plate count requirement.